Manganese Stress Adaptation Mechanisms of Bacillus safensis Strain ST7 From Mine Soil - Ran, Xueqin; Zhu, Zhongmei; Long, Hong; Tian, Qun; You, Longjiang; Wu, Xingdiao; Liu, Qin; Huang, Shihui; Li, Sheng; Niu, Xi; Wang, Jiafu (Frontiers in Microbiology, 2021)
The mechanism of bacterial adaption to manganese-polluted environments was explored using 50 manganese-tolerant strains of bacteria isolated from soil of the largest manganese mine in China. Efficiency of manganese removal by the isolated strains was investigated using atomic absorption spectrophotometry. Bacillus safensis strain ST7 was the most effective manganese-oxidizing bacteria among the tested isolates, achieving up to 82% removal at a Mn(II) concentration of 2,200 mg/L. Bacteria-mediated manganese oxide precipitates and high motility were observed, and the growth of strain ST7 was inhibited while its biofilm formation was promoted by the presence of Mn(II). In addition, strain ST7 could grow in the presence of high concentrations of Al(III), Cr(VI), and Fe(III). Genome-wide analysis of the gene expression profile of strain ST7 using the RNA-seq method revealed that 2,580 genes were differently expressed under Mn(II) exposure, and there were more downregulated genes (n=2,021) than upregulated genes (n=559) induced by Mn stress. KAAS analysis indicated that these differently expressed genes were mainly enriched in material metabolisms, cellular processes, organism systems, and genetic and environmental information processing pathways. A total of twenty-six genes from the transcriptome of strain ST7 were involved in lignocellulosic degradation. Furthermore, after fifteen genes were knocked out by homologous recombination technology, it was observed that the transporters, multicopper oxidase, and proteins involved in sporulation and flagellogenesis contributed to the removal of Mn(II) in strain ST7. In summary, B. safensis ST7 adapted to Mn exposure by changing its metabolism, upregulating cation transporters, inhibiting sporulation and flagellogenesis, and activating an alternative stress-related sigB pathway. This bacterial strain could potentially be used to restore soil polluted by multiple heavy metals and is a candidate to support the consolidated bioprocessing community.